Genome-Wide Identification of GLK Family Genes in Phoebe bournei and Their Transcriptional Analysis Under Abiotic Stresses - Lian, Yiran; Peng, Liang; Shi, Xinying; Zheng, Qiumian; Fan, Dunjin; Feng, Zhiyi; Liu, Xiaomin; Ma, Huanhuan; Cao, Shijiang; Chang, Weiyin (International journal of molecular sciences, 2025)
GOLDEN2-LIKE (GLK) transcription factors are crucial regulators of chloroplast development and stress responses in plants. In this study, we investigated the GLK gene family in Phoebe bournei (Hemsl.) Yen C. Yang, a near-threatened species important for forestry and wood utilization in China. We identified 61 PbGLK genes which were classified into seven subfamilies. Our analyses of their phylogenetic relationships, gene structures, and chromosomal distribution revealed diverse characteristics. Expression profiling under different tissues and abiotic stresses showed that PbGLK25 and PbGLK30 were particularly responsive to drought, heat, light, and shade stresses, with significant upregulation. These findings highlight the potential role of PbGLK genes in stress adaptation and provide insights for the genetic improvement of P. bournei.